Sex differences in the radiographic and symptomatic prevalence of knee and hip osteoarthritis - Faber, Benjamin G.; Macrae, Fiona; Jung, Mijin; Zucker, Benjamin E.; Beynon, Rhona A.; Tobias, Jonathan H. (Frontiers in Endocrinology, 2024)
Recognising sex differences in disease prevalence can lead to clues as to its pathogenesis, for example the role of hormonal factors and related influences such as body composition, as well as forming the basis for new treatments. However, if different methods are used to define the disorder it can be difficult to explore differences in prevalence, making it necessary to draw on multiple sources of evidence. This narrative review addresses sex differences in the prevalence of knee and hip osteoarthritis, which are the most common forms of large joint osteoarthritis. Females appear to have a higher prevalence of knee osteoarthritis across a wide range of disease definitions, while findings for the hip vary depending on how the disease is defined. Clinically or symptomatically defined hip osteoarthritis is more common in females, whereas radiographically defined hip osteoarthritis is more common in males. Therefore, understanding sex differences in large joint arthritis requires consideration that osteoarthritis, as defined structurally, more commonly affects females at the knee, whereas the opposite is true at the hip. Furthermore, despite structural changes in hip osteoarthritis being more common in males, symptomatic hip osteoarthritis is more common in females. The basis for these disparities is currently unclear, but may reflect a combination of hormonal, biomechanical and behavioural factors.